Repeated sprint ability in elite basketball players: the effects of 10 × 30 m vs. 20 × 15 m exercise protocols on physiological variables and sprint performance - Figueira, B.; Gonçalves, B.; Abade, E.; Paulauskas, R.; Masiulis, N.; Kamarauskas, P.; Sampaio, S. (Journal of Human Kinetics, 2021)
Team sports players are required to perform repeated bouts of short-term high-intensity actions during the games. The present study aimed to examine the effects of a novel repeated sprint ability protocol (20×15 m) and compare it with the impact of a more traditional repeated sprint ability protocol (10×30 m). Twelve male elite Lithuanian basketball players (age 21.0 ± 2.0 y, body height 1.90 ± 0,07 m, body mass 86.2 ± 5.8 kg and training experience 12.0 ± 1.9 y) competing in the Lithuanian National Basketball Championship participated in this study. Participants completed three bouts of each repeated sprint protocol interspersed with 5 minutes of recovery. Results showed that the 20×15 m protocol caused a significant decrease in total sprint time (most likely; mean changes (%) with ± 90% of confidence limits, -9.4%; ± 0.7%) and a large decrease in blood lactate (most likely, -39.2%; ±12.8%) compared to the 10×30 m protocol. Despite small differences, the fatigue index presented a similar trend (possibly decrease, -23.7%; ± 38.8%). The exercise heart rate showed a very similar trend with trivial differences between the two protocols. The 20×15 m protocol presented a lower heart rate during recovery with small magnitude. Overall, the present study showed that the 20×15 m protocol seemed to be more representative of the specific basketball demands. Coaches should be aware that RSA training during the in-season may be an adequate stimulus to improve high-intensity runs and muscle power in high-level players.